Другая метрика: [стихи] / Александр Анашкин - Анашкин Александр Алексеевич (Издательство Руслана Элинина, 2006)
Экземпляры: ф.5 (20180222) / Инвентарный номер: 58066 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: А 64 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5